2013
DOI: 10.1364/oe.21.021485
|View full text |Cite
|
Sign up to set email alerts
|

Colloidal particle lens arrays-assisted nano-patterning by harmonics of a femtosecond laser

Abstract: We consider nanopatterning of dielectric substrates by harmonics of single powerful femtosecond pulses from a Ti:Sapphire laser. The nanopatterning is mediated by closely packed monolayers of polystyrene microspheres that act as microlenses at the surface. Observed modification of the material proceeds via ionization. By our theory, the second harmonic is more effective in multi-photon ionization and is better focused than the fundamental frequency which is effective in multiplying of the amount of free electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 19 publications
2
13
0
Order By: Relevance
“…In the previously studied case of 1-lm diameter, when the fluence of the laser pulse is increased above a certain threshold level (the threshold intensities are about 5 Â 10 11 W=cm 2 for SH þ FF and about 10 12 W=cm 2 for FF; the corresponding threshold fluences are 25 mJ=cm 2 and 50 mJ=cm 2 ), the spheres are eliminated from the substrate within the irradiated area. 18,19 This process is similar to the cleaning phenomenon. 26,27 When increasing the fluence up to 15% above the cleaning threshold, welldefined structures are obtained.…”
mentioning
confidence: 75%
See 2 more Smart Citations
“…In the previously studied case of 1-lm diameter, when the fluence of the laser pulse is increased above a certain threshold level (the threshold intensities are about 5 Â 10 11 W=cm 2 for SH þ FF and about 10 12 W=cm 2 for FF; the corresponding threshold fluences are 25 mJ=cm 2 and 50 mJ=cm 2 ), the spheres are eliminated from the substrate within the irradiated area. 18,19 This process is similar to the cleaning phenomenon. 26,27 When increasing the fluence up to 15% above the cleaning threshold, welldefined structures are obtained.…”
mentioning
confidence: 75%
“…Previously, 18,19 we have studied the surface nanostructuring of polymers and glasses by single femtosecond laser pulses using colloidal arrays of 1-lm diameter polystyrene spheres. It is demonstrated that conversion of only 5% of the laser pulse energy into the second harmonic (SH), i.e., irradiation by bichromatic pulses, reduces the laser nanostructuring threshold of polymers and decreases the transverse size of elementary structures, e.g., ablation craters.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These resonances can provide hot spots in the near field around the particle for nanomanufacturing. For example, silica micro-/nanospheres-assisted laser fabrication has been widely investigated in the formation of sub-wavelength features. It has been reported that the use of CPLA can enhance the local light intensity to enhance the laser ablation . A monolayer of micro-/nanospheres on the sample surface acts as an array of near-field lenses that focus the incident light into the multitude of distinct spots .…”
mentioning
confidence: 99%
“…For example, silica micro-/nanospheres-assisted laser fabrication has been widely investigated in the formation of sub-wavelength features. It has been reported that the use of CPLA can enhance the local light intensity to enhance the laser ablation . A monolayer of micro-/nanospheres on the sample surface acts as an array of near-field lenses that focus the incident light into the multitude of distinct spots . Previous extensive studies focused on the nanostructures fabrication on the substrate using low laser pulse energy; however, the strong ablation of the CPLA-deposited substrate using high pulse energy has not been investigated.…”
mentioning
confidence: 99%